Interpretation Of Legal Philosophy Of Contemporary Law - Patrick Winson Salim; Dimas Candra; Rasji Rasji (Jurnal Indonesia Sosial Teknologi, 2023)
Law is an inseparable element of human life. Over time, the law undergoes significant changes to adapt to changes in society and social progress. This transformation has created various contemporary legal issues that require deep philosophical understanding. The interpretation of legal philosophy plays a central role in addressing the challenges of contemporary law. This approach not only provides profound insights into the philosophical dimensions of the law but also helps to understand how contemporary law changes and adapts to the dynamics of society and the development of social progress. Legal philosophy is a discipline that seeks to find truth or a deeper understanding of the law. In this context, legal philosophy is not only concerned with technical aspects or concrete legal regulations but also seeks a broader understanding of the values, ethics, morality, justice, and underlying purposes of the law. This research aims to explain "How can the application of the interpretation of legal philosophy address contemporary legal challenges?" This analysis takes a literature study approach as the basis for the paper's preparation. The findings of the exploration indicate that the interpretation of legal philosophy allows for deep critical thinking about contemporary legal issues, helps identify underlying values, and formulates better and fairer solutions to these problems